Economic Growth, Energy Consumption and Environmental Pollution in Nigeria: Evidence from ARDL Approach - Musa, Kabiru Saidu; Maijama’a, Rabiu (Energy Economics Letters, 2020)
The objective of this paper is to investigate the influence of economic growth and energy consumption on environmental pollution in Nigeria for over 1981-2014 periods and utilized Augmented Dickey Fuller (ADF) and Philip Perron (PP) unit root tests together with Autoregressive Distributed Lag (ARDL) Model in the process of achieving the desire objective. The outcome revealed that all the variables were stationary at first difference and cointegrated whereas the long-run outcome revealed that economic growth and energy consumption have significant positive effects on environmental pollution and this implies that increasing economic growth and energy consumption are responsible for the increasing level of environmental pollution while crude oil price has negative and significant influence on environmental pollution which implies that crude oil price reduces environmental pollution in the long-run. All the short-run outcomes corroborate their long-run counterparts. Nigeria government should emphasis more on the consumption of renewable energy in order to lessen the damaging impacts of economic activities and fossil fuels energy consumption on the quality of the country’s environment.